IDEOLOGY ANALYSIS AS A SOCIO PHILOSOPHICAL PRINCIPLE - Mamatov Obidkhon Vaqqosovich (Modern American Journals, 2025)
This article considers ideology as a fundamental principle for analyzing society. It demonstrates that by analyzing the dominant ideology within a society, it is possible to comprehend the nature of that society. Furthermore, the characteristics of authenticity and falsity within ideology are substantiated.
Keywords: Ideology, social theory, socio-philosophical principle, Frankfurt School, pre-ideological era, ideological era, nationality and universality, interests.